Analisis Kelayakan Usaha Budidaya Selada Krop di CV. Cantigi Desa Cikandang Kecamatan Cikajang Kabupaten Garut - Anne Rizky Ramadhanty; Sulistyodewi Nur Wiyono; Kuswarini Kusno; Lucyana Trimo (Forum Agribisnis, 2020)
Lettuce head as a vegetable commodity has a high enough business opportunity, seen from the developmentof hotels and restaurants in Indonesia that serve foreign cuisine using lettuce. The purpose of this study wasto determine the feasibility of lettuce head farming in CV.Cantigi. This research was carried out inCV.Cantigi, Cikandang village, Cikajang District, Garut Regency. The design of this research is descriptivequantitative with the research technique is a case study The method of data collection is done by interviewswith informants, observations, and literature studies. The determination of the informant was carried outpurposive. Analysis of the data used is non-financial feasibility and financial feasibility (Net Present Value,Internal Rate of Return, Net Benefit/Cost Ratio, Payback Period, and Profitability Ratio). The results showedthat 1) The income of lettuce head farming in CV.Cantigi in one growing season is IDR 120.821.846; 2) Thelettuce head farming in CV. Cantigi is feasible in terms of market aspects, technical aspects, managementaspect, and social, economic, cultural and environmental aspects. Similarly, financially, lettuce headfarming in CV.Cantigi is feasible to do with an NPV value of IDR 286,076,736.8, IRR 51,87%, Net B/C Ratiois 4.32, Payback period occurs at 8 years 8 months and profitability ratio of 101.78%. Suggestions forfurther research there is further research on production technologies that can optimize the use of otherproduction factors to increase production results.